Perilaku Informasi Seniman Digital terhadap Karya Artificial Intelligence di Media Sosial - Ferrensya, Anindita; Irawati, Indira (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2026)
The rapid development of AI has introduced new capabilities, including generating artwork without direct human intervention. However, this advancement has also raised concerns in the art world, such as unauthorized use of artists’ works and the potential decline of human creative labor. This study examines the information behavior of digital artists who are students at the University of Indonesia toward AI-generated artwork, using Wilson’s Model of Information Behavior (1996). A descriptive qualitative method was employed, with data collected through structured interviews with five informants and literature review, and analyzed using thematic analysis. The findings show that participants generally held an anti-AI stance, shaped largely by their social media information behavior. They were influenced by professional artists, both local and international, who expressed criticism of AI-generated art. Consequently, participants tended to reject AI-related content by blocking or reporting accounts and avoiding exposure to such works. This study highlights the need for appropriate policies, as AI directly impacts certain groups in society.